Common variants in LEPR, IL6, AMD1, and NAMPT do not associate with risk of juvenile and childhood obesity in Danes: a case–control study. Issue 1 (December 2015) - Hollensted, Mette; Ahluwalia, Tarunveer; Have, Christian; Grarup, Niels; Fonvig, Cilius; Nielsen, Tenna; Trier, Cæcilie; Paternoster, Lavinia; Pedersen, Oluf; Holm, Jens-Christian; Sørensen, Thorkild; Hansen, Torben
Abstract Background Childhood obesity is a highly heritable disorder, for which the underlying genetic architecture is largely unknown. Four common variants involved in inflammatory-adipokine triggering (IL6 rs2069845, LEPR rs1137100, NAMPT rs3801266, andAMD1 rs2796749) have recently been associated with obesity and related traits in Indian children. The current study aimed to examine the effect of these variants on risk of childhood/juvenile onset obesity and on obesity-related quantitative traits in two Danish cohorts. Methods Genotype information was obtained for 1461 young Caucasian men from the Genetics of Overweight Young Adults (GOYA) study (overweight/obese: 739 and normal weight: 722) and the Danish Childhood Obesity Biobank (TDCOB; overweight/obese: 1022 and normal weight: 650). Overweight/obesity was defined as having a body mass index (BMI) ≥25 kg/m2 ; among children and youths, this cut-off was defined using age and sex-specific cut-offs corresponding to an adult body mass index ≥25 kg/m2 . Risk of obesity was assessed using a logistic regression model whereas obesity-related quantitative measures were analyzed using a general linear model (based onz- scores) stratifying on the case status and adjusting for age and gender. Meta-analyses were performed using the fixed effects model. Results No statistically significant association with childhood/juvenile obesity was found for any of the four gene variants among the individual or combined analyses (rs2069845 OR: 0.94 CI: 0.85–1.04; rs1137100 OR: 1.01 CI: 0.90–1.14; rs3801266: 0.96 CI: 0.84–1.10; rs2796749 OR: 1.02 CI: 0.90–1.15;p  > 0.05). However, among normal weight children and juvenile men, theLEPR rs1137100 A-allele significantly associated with lower BMI (β = −0.12, p  = 0.0026). Conclusions TheIL6, LEPR, NAMPT, andAMD1 gene variants previously found to associate among Indian children did not associate with risk of obesity or obesity-related quantitative measures among Caucasian children and juvenile men from Denmark.